MICROBIOLOGICAL QUALITY OF HEPATOPROTECTIVE HERBAL MEDICINES - Мukhitdinova, К.Sh. (International Journal of Psychosocial Rehabilitation, 2020)
Phyto therapy in many cases has no side effects and toxicity, unlike synthetic medicines. Researches on hepatoprotective phytopreparations and determination of the important indicator Microbiological quality will contribute to the benefit of the phytotherapy for the treatment of hepaticdiseases. The purpose of the research is to analyze and determine the microbiological quality of liquid and dry extract, and coated tablets which have been developed on the basis of the noted above herbals with hepatoprotective activity. Materials and methods. Microbiological quality was determined by the method, described in SP XI, 2nd edition, page 193, change 2, dated 12.10.2005, category 3B, by the indicator “Microbiological quality”. Results show that the liquid and dry extract as well as the coated tablets comply with the SP requirements by the indicator “Microbiological Quality”. The results are included in the drafts of temporal pharmacopoeia article for the presented medicinal forms.